Pola latihan kuda pacu di Desa Pinabetengan dan Pinabetengan Selatan Kecamatan Tompaso Barat - Singal, C.; Ngangi, L.R.; Lapian, H.F.N.; Rimbing, S.C. (Universitas Sam Ratulangi, 2021)
RACE HORSE TRAINING PATTERNS IN PINABETENGAN VILLAGE AND SOUTH PINABETENGAN, WEST TOMPASO DISTRICT. This study aims to look at the training patterns of racehorses in Pinabetengan and South Pinabetengan villages, West Tompaso sub-district. The research material used in this study was race horse livestock in Pinabetengan and South Pinabetengan villages. Horses that were sampled were racehorses that were still active. The number of samples taken in South Pinabetengan village was 11 trains, while in Pinabetengan village there were 14 tails. There were differences in the number of exercises and the duration of the exercises using the trot, canter and gallop patterns in Pinabetengan and South Pinabetengan villages while the walking patterns were exactly the same. In the implementation of patterns and exercises between Pinabetengan and South Pinabetengan villages, Pinabetengan tends to apply more daily training with trot, canter and gallop patterns, while South Pinabetengan villages apply more trot, canter and gallop pattern precursors.Keywords: Race horse, exercise pattern, Pinabetengan dan South Pinabetengan village